Ocular hazards of curing light units used in dental practice – A systematic review - Raniya A. Alasiri; Hashim A. Algarni; Reem A. Alasiri (Saudi Dental Journal)
Objective: To examine the literature and summarize studies that describe the potential ocular hazards that are posed by different systems of light curing units mainly used in the dental clinics, to ensure the safety of the operator, patient and the auxiliary staff in the dental clinic. Methods: This systematic review was reported and conducted according to the PRISMA guidelines. The online databases PubMed and Google Scholar were used for data search. MeSH terms were used for PubMed search. Randomized controlled clinical trials, original studies and in-vitro studies conducted up to 2018 in English language were included in the review. Eight articles were included in the study after application of eligibility criteria, all of which were in accordance to the review protocol. Results: The total wavelength dose received can cause Ocular damage which suggest that light intensity is correlated to the duration required to cause a certain level of damage, and we can substitute the long light exposure by using of a lower intensity light. Conclusion: This review concludes that blue light poses maximum risk to cause retinal degeneration based on the evaluated studies. Most of the studies recommend the use of protective eyewear in order to limit exposure of the patient, operator and assistant to the LCUs. It is not advisable to stare directly into the light source and the recommended safe exposure times and distances for patient, operator and assistant must be strictly adhered to in the dental practice. Keywords: Blue light, Dental curing light, Ocular hazards, Radiation